Simulation of nanoparticle deposition from plasmas on solid surface - Bondar, M.A.; Kravchenko, O.Yu. (Вопросы атомной науки и техники, 2018)
In this paper a computer simulation of depositing nanoparticles from rarefied plasma on a solid substrate, which is at a floating potential, is carried out. In our model, we used the equation of cold hydrodynamics for ions, the equilibrium distribution of Boltzmann for electrons, and the particle in cell method for modeling nanoparticles. Dust particles are charged by electron and ion currents, which are described in accordance with the orbit-limited motion approach. Calculations were performed for various radii of nanoparticles, their concentrations and directed velocities in the unperturbed plasma. The results of the simulation show that, at a sufficiently large size of nanoparticles in the area of the sheath, a dust cloud, whose position changes in time, is formed. This leads to the formation of a minimum of the potential of the electric field and to the change in the structure of the sheath. The modification of the sheath by nanoparticles results in reflection and oscillation of the particles, which causes not stationary flow of nanoparticles onto the substrate.